Study on Changes in Fishing in Anzali Lagoon (1992-1996) - A. Valipor; D. Haghighi (‬‭Majallah-i ̒Ilmī-i Shīlāt-i Īrān, 1998)
According to 5 years period from 1992 to 1996 the total catch in 1992-1996 was 2335158 kg with annual average of 467032 kg, and the catch during years of 1989, 90, 92, 93, 94, 95 and 96 was 100, 314, 598, 630 and 367 ton respectively. The maximum catch in this five years was in Autumn (131146 kg) and in October (50024 kg) and the minimum catch was in winter (98444 kg) and April (29482 kg). C auratus, E lucius and C carpio with 40%, 17.6% and 15% constitute the most catch respectively. The presence of S. lucioperca, A. brama, R frisii kutum, R. rutilus, A. boyeri and C wagneri in the catch indicate that biological condition of lagoon is toward amelioration.